2020
DOI: 10.3390/agronomy10070992
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Evolution to EPSPS Inhibiting Herbicides in False Barley (Hordeum murinum) Harvested in Southern Spain

Abstract: A failure of the EPSPS-inhibiting herbicide glyphosate to control several populations of Hordeum murinum subsp. leporinum (or H. murinum) occurred in southern Spain after more than fifteen applications in both crop (olive, orchards, and citrus) and non-crop (dry areas, roadsides and ditches) areas. Eight out of 18 populations studied were resistant (R) to glyphosate with R factors higher than four based on GR50. These populations also had the highest values of LD50 and the lowest levels of shikimic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Thus, this herbicide has been successfully and extensively used in a broad range of agricultural and non-agricultural areas both against monocot and dicot weeds [7]. Glyphosate in its various formulations has been continuously applied, especially in recent 2 of 12 decades, in orchards, vineyards, olive groves and cereal fields in many countries of the Mediterranean basin [3,8]. As a weak acid, glyphosate needs to be applied in a form of salt, with the isopropylamine, potassium and ammonium salts among the common formulations [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this herbicide has been successfully and extensively used in a broad range of agricultural and non-agricultural areas both against monocot and dicot weeds [7]. Glyphosate in its various formulations has been continuously applied, especially in recent 2 of 12 decades, in orchards, vineyards, olive groves and cereal fields in many countries of the Mediterranean basin [3,8]. As a weak acid, glyphosate needs to be applied in a form of salt, with the isopropylamine, potassium and ammonium salts among the common formulations [1].…”
Section: Introductionmentioning
confidence: 99%
“…The crops with the largest irrigated area are olive groves, citrus-trees, rice (flooding irrigation), wheat, and corn under direct sowing, as well as orchards and lately, for the last 20 years, new almond-tree plantations in an intensive regime. The use of glyphosate for many years under the row in perennial crops and also in fallow fields imposed massive selection pressure on the treated weeds, leading to the emergence of resistance, mainly in Mediterranean Europe ( González-Torralva et al, 2012 , 2014 ; Fernández-Moreno et al, 2017a , b ; Amaro-Blanco et al, 2018 ; Vázquez-García et al, 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…This research also concluded that RF based in GR 50 values separated these 13 populations in three groups, S, R, and VR ( Figure 2 ). All resistant populations had values greater than 4, a requirement to be considered resistant ( Heap, 2020 ; Vázquez-García et al, 2020a ). In addition, the LD 50 is widely employed to determine the herbicide rate need to kill the individuals of a weed population at 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyphosate is the most used herbicide and, in some cases, the only weed control tool, which is applied up to four times a year in high doses (≥720 g ae ha −1 ) [3]. In susceptible plants, this herbicide inhibits the activity of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS), causing the accumulation of shikimic acid [9,10]. Extensive and excessive use of glyphosate to control weeds has led to select at least 45 species with resistance to this herbicide in the world [9,11].…”
Section: Introductionmentioning
confidence: 99%